Ecological Insights Into Community Interactions, Assembly Processes and Function in the Denitrifying Phosphorus Removal Activated Sludge Driven by Phosphorus Sources - Zheng, Lei; Wang, Xue; Ding, Aizhong; Yuan, Dongdan; Tan, Qiuyang; Xing, Yuzi; Xie, En (Frontiers in Microbiology, 2021)
The microbial characteristics in the wastewater treatment plants (WWTPs) strongly affect its optimal performance and functional stability. However, a cognitive gap regarding the characteristics of the microbial community driven by phosphorus sources, especially co-occurrence patterns and community assembly based on phylogenetic group. In this study, fifty-nine denitrification phosphorus removal (DPR) activated sludge samples were cultivated with phosphorus sources (seven inorganic phosphates (IPs), nine cyclic nucleosides phosphates (cNMPs), fourteen nucleosides monophosphates (NMPs), and twenty-nine other organic phosphates (OPs)). The community assembly mechanism based on phylogenetic groups was inferred by Infer Community Assembly Mechanisms by Phylogenetic-bin-based null model (iCAMP). The results suggested that homogeneous selection accounted for the largest proportion (cNMPs: 35.82%, IPs: 64.48%, NMPs: 57.99%, OPs: 54.30%), while dispersal limitation (cNMPs: 33.89%) and drift (IPs: 30.05%, NMPs: 29.95%, OPs: 29.89%) were the most important stochastic process in communities, respectively. Deterministic processes dominated in 12 microbial groups (bins), Candidatus_Accumulibacter and Pseudomonas in these bins were belonged to phosphate-accumulating organisms (PAOs). Network analysis revealed species interactions were intensive in cNMPs influenced microbiota. Function predicted indicated that cNMPs increased the activity of enzymes related to denitrification and phosphorus metabolism, and increased the α-diversity of microorganism, but decreased the diversity of metabolic function. Based on these results, it was assumed that cNMPs, rather than IPs, are the most available phosphorus source for majority microorganisms in DPR activated sludge. The study revealed the important role of phosphorus source in the construction and assembly of DPR microbial communities and provided new insights about pollutant removal from WWTPs.